(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
The design of high entropy alloys (HEAs) is a paradigmatic shift in the development and design of novel alloys with novel properties unmatched by conventional alloys. Due to their superior properties, HEAs are promising candidates for use in wide range of new engineering applications. This paper briefly review the metallurgical nature of (HEAs), including novel properties, areas of application; and influence of alloying elements on HEAs. It can be divided into five main sections. The first section focuses on HEAs, identifying and discussing metallurgical nature of HEAs. This section is followed by detailed reviews on novel properties of HEAs. Areas of applications of HEAs discussed in the third section. The fourth section review the influence of alloying elements on the microstructure and mechanical properties of HEAs. Finally, the metallurgical nature of HEAs and its properties, applications, and influence of alloying elements is concluded. Summarizing the findings from literature.